Cardioprotective effect of Yiqi Huoxue decoction on post-myocardial infarction injury mediated by Ca2+ flux through MAMs - Li, Yufei; Du, Tianhui; Zhang, Yunshu; Lu, Yang; Li, Xinyi; Xie, Weibin; Guo, Shuwen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMitochondria-associated membranes (MAMs) regulate cellular Ca2+ and contribute to cardiovascular disease pathogenesis. The IP3R-GRP75-VDAC1 complex is the primary MAMs pathway regulating Ca2+ flux and cardiomyocyte calcium homeostasis. Yiqi Huoxue decoction (YQHX), a Traditional Chinese Medicine formula, shows potential for myocardial infarction (MI) prevention and treatment. However, YQHX's regulation of MAMs and associated Ca2+ mechanisms in MI remains unclear.MethodsMI rat and oxygen-glucose deprivation cardiomyocytes model were used to mimic myocardial ischemia in human. in vivo, Rats were randomly divided into Sham, Model, YQHX (8.2 g/kg) and Perindopril (10 mg/kg) groups. 28 days after MI, echocardiography, HE, Masson staining and transmission electron microscopy detections were performed to observe cardiac functions and morphology. The effects of YQHX on H9c2 cell viability, mPTP and Ca2+ levels were examined in vitro. Proteins located at MAMs including Cyclophilin D (CypD), Mitochondrial Calcium Uniporter (MCU), Sigma-1 Receptor (Sig-1R), and Neurite Outgrowth Inhibitor B (NOGO-B) are abundantly expressed in myocardial tissue. Consequently, these proteins, along with components of the IP3Rs-GRP75-VDAC1 complex, were detected using WB and qPCR. Mitofusin 2 (Mfn2), which regulates mitochondrial function and Ca2+ flux and is widely expressed at MAMs, was assessed using immunofluorescence.MKT-077, an agent known to disrupt the IP3Rs-GRP75-VDAC1 complex, was employed to investigate the mechanism of YQHX on the complex.ResultsYQHX improved cardiac function and attenuated pathological changes in vivo. It ameliorated MAMs ultrastructure and function, enhancing CypD, MCU, Sig-1R, and NOGO-B expression while reducing IP3R2, GRP75, and VDAC1. in vitro, YQHX significantly increased viability, reduced oxygen-glucose deprivation-induced mPTP opening and Ca2+ levels, upregulated CypD, MCU, Sig-1R, and NOGO-B, and downregulated IP3R2, GRP75, and VDAC1. YQHX also restored MAMs morphology, decreased mPTP opening and Ca2+ levels, and reversed GRP75 downregulation blocked by MKT-077 under oxygen-glucose deprivation.ConclusionsYQHX exerts cardioprotection against hypoxia by regulating Ca2+ homeostasis and preserving MAMs structure, function, and associated protein expression.